Smart cement : development, testing, modeling and real-time monitoring - Vipulanandan, Cumaraswamy, 1956- (Boca Raton, FL : CRC Press, 2021)
"Smart cement is a chemo-thermo-piezoresistive material that functions as a highly sensing 3-dimensional bulk sensor. It can be used for monitoring changes oflectrical resistivity in concrete by the addition of 0.03% of selected conductive or semi-conductive fibers are added to the bulk cement"--
Includes bibliographical references and index.
H.B
Keywords: Cement; Concrete -- Additives; Concrete -- Testing; Smart materials